Early Psychological Intervention After Rape: A Feasibility Study - Bragesjö, Maria; Larsson, Karin; Nordlund, Lisa; Anderbro, Therese; Andersson, Erik; Möller, Anna (Frontiers in Psychology, 2020)
Rape is the most common trauma leading to post-traumatic stress disorder (PTSD) among women, with a conditioned prevalence of up to 50 %. PTSD is considered to be a lethal condition associated with increased risk of suicide, drug-and alcohol dependence, neurological-and vascular problems as well as sick leave. Given the scope of this problem, novel and swiftly delivered interventions for this large vulnerable population is clearly warranted. One previous trial conducted in the US (N=137) showed that an adapted brief version of prolonged exposure (PE) to the fearful memory of the event and situations, provided in the immediate aftermath after trauma (<72 hours after a traumatic event), was effective in reducing early PTSD symptoms in rape victims. The aims of the present study were to adapt the brief PE protocol to a Swedish context and investigate its feasibility and delivery in ten executive patients recruited at the Emergency Clinic for Rape victims in Stockholm. Ten participants were provided with three sessions of early PE with overall successful results in terms of session attendance, home-work compliance and also symptom reduction of PTSD-and depressive symptoms. However, only a fraction of the screened patients at the Emergency clinic (5.2%) were eligible to be included in the study, where the majority (40%) were excluded due to the time criteria of 72 hours. In this paper, we will present detailed results of the intervention and elaborate on how to increase feasibility of preventive interventions for rape victims. In the current form, providing PE with the strict time criteria was not feasible in the clinical setting that constitutes the Emergency department for rape.